Case Report: Solitary scalp metastasis after surgery for invasive ductal carcinoma of the breast - Cheng, Chong; Wang, Tiejun (Frontiers in Oncology, 2025)
BackgroundBreast cancer is one of the most common malignancies among women, and more than 90% of breast cancer-related deaths attributed to metastasis. Cutaneous metastases are relatively uncommon, and scalp involvement is exceedingly rare. Because of its atypical clinical presentation, scalp metastasis is often recognized and diagnosed only after a delay.Case presentationWe report the case of a 45-year-old woman diagnosed with invasive ductal carcinoma (IDC) of the right breast with ipsilateral axillary lymph node involvement (clinical stage cT4bN3M0). The patient received six cycles of neoadjuvant chemotherapy and achieved a partial response (PR) according to RECIST 1.1 criteria. Subsequently, she underwent a right simple mastectomy with axillary lymph node dissection. Pathology demonstrated a Miller–Payne grade 3 response, with metastases identified in all 13 dissected axillary lymph nodes (13/13). Immunohistochemistry (IHC) revealed estrogen receptors (ER) and progesterone receptors (PR) positivity, human epidermal growth factor receptor-2 (HER2) expression of 0, and Ki-67 expression of 20%. She subsequently received adjuvant radiotherapy and endocrine therapy. Surveillance imaging during follow-up showed no evidence of recurrence or distant metastasis. In December 2023, the patient developed a painless, round, skin-colored nodule on the left frontal scalp, accompanied by diffuse right periorbital edema and headache. Over the following year, she was evaluated in dermatology, neurosurgery, and oncology clinics. However, breast cancer metastasis was not initially suspected, resulting in misdiagnosis and delayed treatment. In April 2025, fine-needle aspiration of the scalp nodule confirmed metastatic carcinoma. IHC showed ER and PR positivity, HER2 expression of 1+, and Ki-67 expression of 35%. No additional metastatic lesions were identified. The patient was started on systemic therapy with fulvestrant plus dalpiciclib, and after four cycles, she achieved marked regression of the scalp lesion along with resolution of periorbital edema. The most recent examination, however, detected meningeal and calvarial metastases. Consequently, the patient received localized radiotherapy to these sites while continuing the original treatment protocol.ConclusionThis case highlights the diagnostic challenges of atypical scalp metastases in breast cancer and underscores the importance of early detection and prompt initiation of comprehensive treatment.